Probable RBD and association with neurodegenerative disease markers: A population‐based study. Issue 10 (24th July 2015) - Mahlknecht, Philipp; Seppi, Klaus; Frauscher, Birgit; Kiechl, Stefan; Willeit, Johann; Stockner, Heike; Djamshidian, Atbin; Nocker, Michael; Rastner, Verena; Defrancesco, Michaela; Rungger, Gregor; Gasperi, Arno; et al.
Abstract Background The prevalence of rapid eye movement sleep behavior disorder (RBD) and its association with markers of neurodegeneration in the general population are poorly defined. Methods We assessed the prevalence of probable RBD defined by two validated questionnaires, the RBD Screening Questionnaire (RBDSQ) and the Innsbruck RBD‐Inventory (RBD‐I), and studied its associations with clinical and imaging markers for neurodegeneration in the Bruneck Study cohort aged 60 y or older. Results Of the 456 participants without Parkinson's disease, 4.6% (RBDSQ; 95%CI, 3.0%‐7.0%) and 7.7% (RBD‐I; 95%CI, 5.6%‐10.5%) had probable RBD. Probable RBD diagnosed with either of the questionnaires was associated with hyposmia (trend; P < 0.1), anxiety (P < 0.05), depression (P < 0.05), antidepressant use (P < 0.05), and self‐reported non‐motor symptoms (P < 0.01), specifically, dribbling saliva, memory problems, apathy, concentration problems, and anxiety. Conclusions Our findings may provide a basis for future studies intending to identify cohorts at risk for Lewy body diseases through screening of the general elderly population for RBD. © 2015 International Parkinson and Movement Disorder Society